The Influence of Bilingual of Java Native Towards Indonesian Production in Showing Politeness - Neneng Sri Lestari (The Seall Journal, 2022)
Javaness is one of ethnic in Indonesia. Java native is as an Indonesian people also use the Indonesian in daily activity. Indonesian language as a unifier language country is the tool to communicate with another people in this country. Java native also use Indonesian language when they speak with another people that can’t speak java language. The analysis is the influence of java native towards Indonesian production. The result of the analysis shows that the influence of bilingual of java native towards Indonesian production has mixed Java and Indonesian language which its show politeness in speaking. Keywords: Bilingual, java native, politeness.